The use of metacognitive reading strategies by upper secondary school students / Farah Syahida Ahmad - Ahmad, Farah Syahida (2014)
Metacognitive reading strategies are not explicitly taught to upper secondary students in Malaysia. Students are accounted to develop these strategies over the years. Thus,jthe research applied a mix-method design intended to recognise the use of metacognitive reading strategies to support the reading performance of ESL upper secondary school learners and factors involved in the use of metacognitive reading strategies by the participants. The research also aimed to examine the relationship between the use of metacognitive reading strategies and the participants’ performance in reading. A total of sixty participants who study in Form 4 or also known as upper secondary school students from an urban school was chosen randomly for the research. The participants sat for reading proficiency test adopted from Mohammad, Chew, and Kabilan (2006) to determine their proficiency levels. They were divided into high, moderate, and low proficiency levels based on the English Proficiency Index (EPI) adopted from Morley (2010). Then, the participants were to respond to a questionnaire inclusive of Survey of Reading Strategies adopted from Mokhtari and Sheorey (2002). The data from the questionnaires was analysed by using Statistical Package for Social Science (SPSS) Version 16. The quantitative results indicated that participants of varied proficiency levels demonstrated different types and frequency for the use of metacognitive reading strategies. It was also learnt that there was positive relationship between the use of metacognitive reading strategies and their reading performance. Fifteen participants were chosen selectively for interview sessions to obtain factors for high and low usages of metacognitive reading strategies. The qualitative results showed that there were several determining factors that contributed to high and low usage of the metacognitive reading strategies. This study concludes by discussing pedagogical implications of the findings at the end. The implications are metacognitive reading strategies must be taught to students in upper secondary and teachers must provide recursive sustaining situations and activities in language classes to ensure learners apply the metacognitive reading strategies. Along the way, teachers must be cautious about the materials and texts used in providing grounds for learners to practice the use of strategies while reading.